Financial Technology: From Temporary Disruption to New Financial Industry Model - Andrew Djauhary; Florentina Kurniasari; Mulyono Mulyono (Profesional Muda Cendekia Publishing, 2022)
The digital transformation process in business has impacted every business globally. Unfortunately, the Covid-19 pandemic is adding to the pressure to exist even worse in situation. The research study is taking the impact of the disruptive financial technology services on sustaining the Small and Medium Enterprise during the pandemic. Using the study in Indonesia’s financial industry performance, the researcher wanted to find out the variables that able to sustain the temporary function of digital business into a permanent transformation of business function. A close look at the literature of company performance reveals that different variables have been used by the researchers to influence the performance of a company. They are human capital, customer orientation, and dynamic capability. However, the research has limitation for multi-group analysis, thus the researcher suggest that further study need to be continue to update changes that is not relevant in the future.